Biofunctional ionic-doped calcium phosphates: silk fibroin composites for bone tissue engineering scaffolding - Pina, S. (2017)
The treatment and regeneration of bone defects caused by traumatism or diseases have not been completely answered by current therapies. Lately, advanced tools and technologies have been successfully developed for bone tissue regeneration. Functional scaffolding materials such as biopolymers and bioresorbable fillers have gained particular attention, owing to their ability to promote cell adhesion, proliferation and extracellular matrix production, promoting new bone ingrowth. Here we present novel biofunctional scaffolds for bone regeneration composed by silk fibroin (SF) and Î²-tricalcium phosphate (Î²-TCP) incorporating Sr, Zn, and Mn that were successfully developed using salt-leaching followed by freeze-drying technique. The scaffolds presented a suitable pore size and porosity, and high interconnectivity that were adequate for promoting cell attachment and proliferation. The degradation behavior and compressive mechanical strengths showed that scaffolds SF/doped TCP exhibit improved characteristics for bone tissue engineering when compared with SF scaffolds alone. The in vitro bioactivity assays using a simulated body fluid showed the growth of an apatite layer. Furthermore, in vitro assays using hASCs presented different responses on cell proliferation/differentiation when varying the doping agents in the biofunctional scaffolds. The incorporation of Zn into the scaffolds led to improved proliferation, while the Sr- and Mn-doped scaffolds presented higher osteogenic potential as demonstrated by DNA quantification and ALP activity. The combination of Sr with Zn led to an influence on cell proliferation and osteogenesis when compared with single ions. The present results indicate that biofunctional ionic-doped composite scaffolds are good candidates for further in vivo studies for bone tissue regeneration.